Influencia de la participación de los padres de familias en la gestión escolar de las instituciones primarias urbanas del distrito de Iquitos 2019 - Puente Casimiro, Areli Eunice (2021)
The general objective of this research was to explain the influence of the participation of parents in the school management of the urban primary educational institutions of the district of Iquitos 2019. The type of study was explanatory and field design, contemporary and univariate. The population consisted of 864 teachers and a sample of 261 teachers at the primary level was used and stratified sampling with proportional allocation was applied, data was collected with the survey technique and the validated questionnaire instrument and with a Cronbach's Alpha coefficient of 91.0%. The results obtained showed that 78.5% of the teachers surveyed consider that the participation of parents in learning and education is deficient, 91.2% of the teachers surveyed consider that the participation of parents in shared management is deficient and 72.8% of the teachers surveyed consider that the participation of parents in community collaboration is deficient in urban primary educational institutions of the district of Iquitos 2019. Likewise, the variables participation of parents in the learning and education of their children, participation of parents in shared management and participation of parents in collaboration with the community have significant influence because the p-value <0.05. The model presents a coefficient of determination of 98.6%.